2015
DOI: 10.1016/j.expneurol.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Defining the critical hypoxic threshold that promotes vascular remodeling in the brain

Abstract: In animal models, hypoxic pre-conditioning confers protection against subsequent neurological insults, mediated in part through an extensive vascular remodeling response. In light of the therapeutic potential of this effect, the goal of this study was to establish the dose-response relationship between level of hypoxia and the extent of cerebrovascular modeling, and to define the mildest level of hypoxia that promotes remodeling. Mice were exposed to different levels of continuous hypoxia (8-21% O2) for seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 38 publications
(69 reference statements)
0
32
0
Order By: Relevance
“…There is a temporal component of the hormetic response, as effects of a highly stressful exposure are typically seen 24 to 72 hours later, and usually present as a modest overcompensation response in which the net result is about 30% to 60% greater than the original starting point or control group value. Such hormetic responses, which are sometimes referred to as a “ceiling response,” may also describe the modest degree of stimulation in the low dose zone (Calabrese et al, ; Calabrese ; Abete et al, ; Boroujerdi and Milner, ).…”
Section: Brain Response In Vad: a Role For Hormetic Effects And Precomentioning
confidence: 99%
See 2 more Smart Citations
“…There is a temporal component of the hormetic response, as effects of a highly stressful exposure are typically seen 24 to 72 hours later, and usually present as a modest overcompensation response in which the net result is about 30% to 60% greater than the original starting point or control group value. Such hormetic responses, which are sometimes referred to as a “ceiling response,” may also describe the modest degree of stimulation in the low dose zone (Calabrese et al, ; Calabrese ; Abete et al, ; Boroujerdi and Milner, ).…”
Section: Brain Response In Vad: a Role For Hormetic Effects And Precomentioning
confidence: 99%
“…For example, following injury, chemical signaling to induce cellular repair processes has been shown to be dependent upon endogenous mechanisms that display concentration gradients that act in a biphasic hormetic pattern (Calabrese, ; Abete et al, ). Similarly, hormetic dose–concentration responses are seen in endothelial cells that interact with the vascular capillary system to optimize biological activities (Boroujerdi and Milner, ).…”
Section: Brain Response In Vad: a Role For Hormetic Effects And Precomentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that individuals repeatedly exposed to subacute hypoxia/ischemia 399 may respond differently to nitrate supplementation due to hypoxic preconditioning. Studies suggest that 400 repeated subacute hypoxic exposure may offer neurovascular protection(Poinsatte et al 2015), 401 cerebrovascular remodeling(Boroujerdi and Milner 2015), and may improve oxygen 402 saturation(Foster et al 2014) and abrogate oxidative stress(Berger et al 2015) during additional 403 ischemic events. Whether hypoxic preconditioning alters the effect of nitrate on NVC and cognitive 404 function in hypoxia was beyond the scope of the current study and requires future research.…”
mentioning
confidence: 99%
“…On the other hand, one study conducted on elderly women with OSA found that risk of mild cognitive impairment and cognitive decline was associated with a higher oxygen desaturation index [23], although another study did not reach the same conclusion, possibly because it included mostly mild to moderate OSA [25]. One possible explanation for the discrepant findings concerning the impact of hypoxemia on brain function could relate to different patterns of chronic intermittent versus more sustained hypoxemia, as well as the severity of hypoxemia [104,118,119].…”
Section: Pathogenesis Of Cognitive Impairment In Osamentioning
confidence: 97%